(untitled) (Journal of Asian Development Studies, 2025)
Educational practices have been positively impacted by Generative Artificial Intelligence (AI) and Large Language Models (LLMs) such as ChatGPT. Unlike traditional systems and learning platforms, ChatGPT engages users in conversations, provides tailored feedback, and creates new knowledge in virtually any area. This paper provides a detailed model for educational practice using ChatGPT and other generative AI systems. The model attempts to address, in an equitable manner, the three most challenging aspects of educational practice: pedagogical concerns, technological availability, and ethical peripherals. The model enhances students’ engagement, promotes the development of their higher-order thinking skills, and is designed to improve learning outcomes through personalization. This paper discusses a conceptual model for adaptive generative tutoring and provides technical illustrations, tables, and formulae to describe the process. The use of generative AI in STEM problem solving and language learning is primary, but the challenges of academic honesty, bias, and data privacy are also addressed. The current paper provides a potential framework for the thoughtful and purposeful use of ChatGPT in educational settings and makes a valuable contribution to the discourse on the intersection of educational technology and the ethics of AI in teaching.